Programmable intelligent spaces for Industry 4.0: Indoor visual localization driving attocell networks. Issue 11 (5th April 2019) - do Carmo, Alexandre P.; Vassallo, Raquel F.; de Queiroz, Felippe M.; Picoreti, Rodolfo; Fernandes, Mariana R.; Gomes, Roberta L.; Martinello, Magnos; Dominicini, Cristina K.; Guimarães, Rafael; Garcia, Anilton S.; Ribeiro, Moises R. N.; Simeonidou, Dimitra
Abstract: Real‐time and mission‐critical applications for Industry 4.0 demand fast and reliable communication. Therefore, knowing devices' location is essential, but GPS is of little use indoors, whereas electromagnetic impairments and interferences demand new approaches to ensure reliability. The challenges include real‐time feedback with end‐to‐end (E2E) low latency; high data density due to large number of IoT devices per area; and smaller communication cells, which increases the handover frequency and complexity. To tackle these issues, we introduce a programmable intelligent space (PIS) to deploy attocells, enable E2E programmability, and provide a precise computer vision localization system and networking programmability based on software‐defined networking. To validate our approach, experiments were conducted, controlling a mobile robot through a trajectory. We demonstrate the need for higher camera frame rate to achieve tighter precision, evaluating different trade‐offs on localization, bandwidth, and latency. Results have shown that PIS wireless attocell handover achieves seamlessly mobile communication, delivering packets within the deadline window, with similar performance to a no handover baseline. Abstract : Real‐time and mission‐critical applications for Industry 4.0 demand fast and reliable communication. The challenges include real‐time feedback with E2E low latency; high data density due to large number of IoT devices per area; and smaller communication cells, which increases the handover frequency and complexity. To tackle these issues, we introduce a programmable intelligent space (PIS) to deploy attocells, enable E2E programmability, and provide a precise computer vision localization system and networking programmability based on SDN.